Design and validity of the Bergen Instagram Addiction Scale (BIAS) in Peruvian adults - Chavez Santamaria, Alexandra (2021)
Virtual social networks have had a notable impact on our lives, and over the years it has led to the creation of new virtual socialization platforms such as Instagram, which in our context has taken great interest, especially in adults young people, occupying a large part of their personal, academic, work and social space, often leading to problematic behaviors such as addiction. The objective of this study was to design and validate the Bergen Instagram Addiction Scale (BIAS), based on the short Spanish version of the Bergen Facebook Addiction Scale (BFAS). 200 Peruvian adult Instagram users from 18 to 35 years old participated (M age = 25.9; SD age = 4.29), 63.5% were women. For the design, the terminology was changed from Facebook to Instagram, in the items of the BFAS, later the AFC was carried out to estimate the evidence of factorial validity and AFC-MG for the invariance of the measurement by sex, checking invariance for all the levels (configural, metric, strong and strict). The instruments were applied; the Psychological Well-being Scale (BIEPS-A) and the Life Satisfaction Scale (SWLS), which were related to the BIAS, corroborating the divergence betweenthe constructs, and the convergence of the BIAS was analyzed as it was correlated with the BFAS (r = .520). The reliability of the instrument was estimated with the Alpha (α = .925) and Omega (ω = .931) coefficients. It is concluded that the BIAS has optimal evidence of validity and reliability, demonstrating a one-dimensional structure for measuring addiction to Instagram.